Incidence of Tracheal Stenosis in Patients after SARS-CoV-2 (Research, Society and Development, 2022)
Tracheal stenosis is clinically defined as a decrease in the tracheal lumen, which can be triggered by several factors. Physiologically, it begins with an inflammatory process after mucosal injury, hyperemia and local edema. Subsequently, the process of repair and healing of the airway takes place, becoming symptomatic when lumen narrowing reaches >60%. The rate of post-intubation tracheal stenosis in non-COVID-19 patients is 10–22%, making it a rare condition with an estimated incidence of 4.9 cases per million per year in the general population. There is still no data on stenosis in recovered COVID patients. This study sought to observe the incidence of post-COVID stenosis at the University Hospital of Western Paraná and, in conclusion, a higher incidence of stenosis was found in female patients, but male patients had greater complications. The death rate was higher in intubated patients compared to tracheostomized patients and the incidence of tracheal stenosis found was relatively low when compared to non-COVID stenosis data found in the literature.